2022
DOI: 10.1142/s1363919622500153
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Innovation Performance and Firm Performance: Examining the Inter-Relationship of Risk-Taking, Risk Management and Open Innovation

Abstract: This study empirically examines how risk-taking and risk management affect open innovation (OI) and innovation performance in terms of new product or service success (NPS) and new product or service innovativeness (NPI) and analyses how OI is related to innovation performance and firm performance, utilising a combination of survey and secondary data. To test the proposed hypotheses, we perform structural equation modelling (SEM) based on a sample of 309 German firms. Our findings show that a higher level of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 168 publications
0
2
0
Order By: Relevance
“…Bromiley et al (2017) argue that for proper risk minimisation, all SMEs control the critical issues, and they try not to leave any space for failure. Durst et al (2019) could empirically show that the management of risks related to knowledge can impact the innovativeness of organisations while Lendowski et al (2022) found in their study of German firms a positive attitude to risk taking activities along with proper RM increases innovation performance. On the other hand, having too tight controls and excessive RM practices in conjunction with innovation activities can reduce the room available for discovering and learning from failures and mistakes, which can affect innovation capacity negatively (Bowers and Khorakian, 2014).…”
Section: Risk Management and Innovation Performancementioning
confidence: 99%
“…Bromiley et al (2017) argue that for proper risk minimisation, all SMEs control the critical issues, and they try not to leave any space for failure. Durst et al (2019) could empirically show that the management of risks related to knowledge can impact the innovativeness of organisations while Lendowski et al (2022) found in their study of German firms a positive attitude to risk taking activities along with proper RM increases innovation performance. On the other hand, having too tight controls and excessive RM practices in conjunction with innovation activities can reduce the room available for discovering and learning from failures and mistakes, which can affect innovation capacity negatively (Bowers and Khorakian, 2014).…”
Section: Risk Management and Innovation Performancementioning
confidence: 99%
“…While some authors claim that high risk-taking attitudes hinder innovation efforts (e.g. Brooks et al ., 2023), others state that a positive attitude to risk taking, coupled with effective risk management, can enhance innovation performance (Lendowski et al ., 2022). Laukkanen and Patala (2014) suggested that an overly negative attitude towards risk hinders successful implementation of BMI.…”
Section: Discussionmentioning
confidence: 99%